2019
DOI: 10.1002/ejoc.201900830
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoconvergent Synthesis of Chiral Diarylmethyl Sulfones by Direct Sulfonylation of Diarylmethanols Diastereomixtures with Sodium Sulfinates Catalyzed by SnBr2

Abstract: A novel synthetic method affording a variety of chiral diarylmethyl sulfones was developed via diastereoconvergent sulfonylation of diarylmethanols diastereomixtures bearing a chiral auxiliary with sodium sulfinates using a SnBr2 catalyst and trimethylsilyl chloride (TMSCl) under mild reaction conditions. The reaction proceeded in a diastereoconvergent pattern via a diarylmethycation intermediate. The chiral auxiliary induced high diastereoselectivity and improved reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The reaction was complete within 1 h, and the desired product 12a was obtained in 83 % yield and with a 97:3 dr (entry 1). We have already reported on the applicability of tin salts as Lewis acids for the diastereoconvergent coupling reactions of 3a with several nucleophiles . Thus, the same reaction was conducted in the presence of several tin salts, namely, SnCl 2 , SnBr 2 , SnCl 4 , and SnBr 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction was complete within 1 h, and the desired product 12a was obtained in 83 % yield and with a 97:3 dr (entry 1). We have already reported on the applicability of tin salts as Lewis acids for the diastereoconvergent coupling reactions of 3a with several nucleophiles . Thus, the same reaction was conducted in the presence of several tin salts, namely, SnCl 2 , SnBr 2 , SnCl 4 , and SnBr 4 .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, many related organocatalytic enantioselective syntheses utilizing quinone methides have been developed, but they are often restricted to substrates containing electron‐donating groups. Preceding this research, we developed a chiral auxiliary and applied it to Lewis acid‐catalyzed chiral inductive diastereoconvergent couplings of diarylmethanol diastereomeric mixtures 3 , employing nucleophiles such as 2‐naphthols, allyltrimethylsilane, benzamides, and sodium sulfinates . It was revealed that these reactions were applicable to a variety of substrates to give products 4 , 5 , 6 , and 7 , respectively (Scheme b).…”
Section: Introductionmentioning
confidence: 99%
“…However, upon investigating the reaction mechanism, it was found that the reaction proceeded via carbocation intermediates, and the obtained products were racemates. Our research group has demonstrated the Lewis acid‐catalyzed diastereoconvergent substitution of diastereomixtures of diarylmethanols 5 bearing chiral auxiliaries using various nucleophiles, such as 2‐naphthols, [21a] allyltrimethylsilanes, [21b] benzamides, [21c] sodium sulfinates, [21d] 1,3‐dicarbonyls, [21e] and sulfonamides, [21f] to produce the corresponding substituted products 6 [Scheme 1, (c)]. In this study, we plan to extend our sulfamidation protocol to chiral products to further increase the versatility of the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Yamamoto and Nakata established the SnBr 2 -catalyzed sulfonylation of chiral auxiliary derived racemic diarylmethanols with sodium sulfinates in the presence of trimethylsilyl chloride (TMSCl) for the synthesis of diastereoselective diarylmethyl sulfones ( Scheme 261 ). 369 Various diarylmethanols with different substituents on the aromatic rings of the substrates were explored systematically with PhSO 2 Na and afforded diarylmethyl sulfones with high diastereoselectivity. The yields and diastereoselectivity were substantially improved by lowering the temperature (−40 °C) or decreasing the catalyst loading for diastereo-convergent sulfonylation.…”
Section: Applications Of Sodium Sulfinatesmentioning
confidence: 99%